MODERASI BERAGAMA, KATOLISISME MANGGARAI DAN EKOLOGI INTEGRAL GEREJA KEUSKUPAN RUTENG - Bandur, Hironimus; Julivadistanto, Thomas; Gambur, Karolina Mutiara (STIPAS St. Sirilus Ruteng, 2024)
This article reveals the religious dynamics of Manggarai and the contribution of the Ruteng Diocese Church in developing the concept and movement of religious moderation in the West Flores region through the integral ecological pastoral programme in 2024. The main question to be sought in this research is how far the religious community in Manggarai (Islam, Catholicism and local belief) shows religious moderation and how the value of religious moderation is developed in the integral ecological pastoral programme. By using qualitative methods with participatory observation research instruments, as well as data analysis through Nurcholis Madjid's thinking framework about passing-over, the author finds that first, basically a moderate society Manggarai is realized when Catholicism breaks away from exclusivism tendencies; second, Manggarai Catholicism was formed from adherents of Islam and local beliefs; and third, the Manggarai Catholic developed the concept and movement of religious moderation in its integral ecological pastoral programme through environmental education and advocacy activities involving all religious communities, which is why the term eco-moderation emerged. Eco-moderation activities are carried out in Muslim center areas such as Papagarang Island, Komodo District, Labuan Bajo, Reo, and Pota, East Manggarai. Through the integral ecological pastoral programme, the Church of Ruteng Diocese is passing-over and at the same time directing religious communities to move beyond religion and religiosity, namely to become post-religious humans. Keywords: Religious Moderation, Catholicism, The catholic church of Ruteng Diocese Tulisan ini mengungkap dinamika keagamaan Manggarai dan kontribusi Gereja Keuskupan Ruteng dalam mengembangkan konsep dan gerakan moderasi beragama di wilayah Flores Barat melalui program pastoral ekologi integral tahun 2024. Pertanyaan pokok yang hendak dicari dalam penelitian adalah sejauh mana komunitas agama di Manggarai (Islam, Katolik dan agama lokal) menampakkan moderasi beragama dan bagaimana nilai moderasi beragama dikembangkan dalam program pastoral ekologi integral. Dengan menggunakan metode kualitatif dengan instrument penelitian observasi partisipatoris, serta analisis data melalui kerangka berpikir Nurcholis Madjid tentang passing-over, penulis menemukan bahwa pertama, pada dasarnya masyarakat moderat terwujud ketika Katolisisme melepaskan diri dari kecenderungan eksklusivisme; kedua, katolisisme Manggarai terbentuk dari penganut Islam dan agama lokal; dan ketiga, Gereja Katolik Manggarai mengembangkan konsep dan gerakan moderasi beragama dalam program pastoral ekologi integral melalui kegiatan-kegiatan edukasi dan advokasi lingkungan hidup yang melibatkan semua komunitas agama, sebab itu muncul istilah eko-moderasi. Kegiatan eko-moderasi dilakukan pada daerah-daerah sentra Muslim seperti di Pulau Papagarang, Kecamatan Komodo, Labuan Bajo, Reo, dan Pota Manggarai Timur. Melalui program pastoral ekologi integral, Gereja Keuskupan Ruteng berpassing-over sekaligus mengarahkan komunitas agama-agama agar bergerak melampaui agama dan keagamaan, yaitu menjadi manusia pasca agama. Kata-kata kunci: moderasi beragama, katolisisme, Gereja Katolik Keuskupan Ruteng